A unique chromosomal in‐frame deletion identified among seven XP‐C patients. Issue 5 (27th July 2016) - Schubert, Steffen; Rieper, Petra; Ohlenbusch, Andreas; Seebode, Christina; Lehmann, Janin; Gratchev, Alexei; Emmert, Steffen
Summary: Background: The nucleotide excision repair (NER) pathway, defective in xeroderma pigmentosum (XP) patients, removes DNA photolesions in order to prevent carcinogenesis. Complementation group C (XP‐C) is the most frequent group of XP patients worldwide. Methods: We analyzed seven XP‐C patients clinically and molecular‐genetically applying: post‐UV cell survival (MTT‐assay), quantitative Real‐time PCR, sequencing on chromosomal as well as cDNA level, and in silico interpretation of sequencing data. Results: All cases displayed diminished post‐UV cell survival as well as reduced XPC mRNA levels. Five homozygous and two heterozygous disease causing mutations were identified. A large chromosomal deletion of ~5.8 kb identified in XP174MA leads to an unique in frame deletion of XPC exon 2 and exon 3. In silico analysis revealed the deletion of 102 amino acids in the N‐terminal part of XPC while leaving the C‐terminal domain intact. The novel c.361delA mutation in XP168MA leads to a frameshift in exon 3 resulting in a premature stop codon 27 codons downstream of the deleted adenine. Conclusion: Our analysis confirms that XP‐C patients without increased sun sensitivity develop non‐melanoma skin cancers earlier than sun‐sensitive XP‐C patients. Reduced cellular mRNA levels are characteristic for XP complementation group C and qRT‐PCR represents a rapid diagnostic tool.